Electrochemical Removal of Nitrogen Compounds from a Simulated Saline Wastewater - Pasquale Iovino; Angelo Fenti; Simona Galoppo; Mohammad Saleh Najafinejad; Simeone Chianese; Dino Musmarra (Molecules, 2023)
In the last few years, many industrial sectors have generated and discharged large volumes of saline wastewater into the environment. In the present work, the electrochemical removal of nitrogen compounds from synthetic saline wastewater was investigated through a lab-scale experimental reactor. Experiments were carried out to examine the impacts of the operational parameters, such as electrolyte composition and concentration, applied current intensity, and initial ammoniacal nitrogen concentration, on the total nitrogen removal efficiency. Using NaCl as an electrolyte, the NTOT removal was higher than Na2SO4 and NaClO4; however, increasing the initial NaCl concentration over 250 mg·L−1 resulted in no benefits for the NTOT removal efficiency. A rise in the current intensity from 0.05 A to 0.15 A resulted in an improvement in NTOT removal. Nevertheless, a further increase to 0.25 A led to basically no enhancement of the efficiency. A lower initial ammoniacal nitrogen concentration resulted in higher removal efficiency. The highest NTOT removal (about 75%) was achieved after 90 min of treatment operating with a NaCl concentration of 250 mg·L−1 at an applied current intensity of 0.15 A and with an initial ammoniacal nitrogen concentration of 13 mg·L−1. The nitrogen degradation mechanism proposed assumes a series–parallel reaction system, with a first step in which NH4+ is in equilibrium with NH3. Moreover, the nitrogen molar balance showed that the main product of nitrogen oxidation was N2, but NO3− was also detected. Collectively, electrochemical treatment is a promising approach for the removal of nitrogen compounds from impacted saline wastewater.